Russian Specialists' Perception of Negotiations with Chinese Partners: Expectations, Strategies and Challenges - Ekaterina D. Vasilyeva; Albina A. Gallyamova; Elizaveta Sh. Komyaginskaya; Nadezhda M. Lebedeva (Peoples' Friendship University of Russia (RUDN University), 2024)
In the context of global challenges and changing geopolitical situations around the world, Russian organizations are increasingly facing the necessity of active cooperation with countries in the Far East, especially China. The purpose of this exploratory study was to identify how Russian business representatives perceive and manage this process, with special attention to expectations and perceptions of communication effectiveness. The study focused on two key aspects: firstly, the analysis of expectations of Russian representatives, which shape their approaches to negotiations, and secondly, the assessment of their perception of the dynamics and effectiveness of these negotiations. The study sample included 13 Russian employees of Russian companies who had experience in negotiations with Chinese partners. The study used semi-structured qualitative interviews. Qualitative content analysis was used to analyze the data. Further coding and analysis of the text were carried out in the Atlas.ti. As a result of the analysis of the interview, the main topics were identified that describe the perception of the negotiation process: expectations regarding the negotiation process, strategies for preparing for negotiations, behavior strategies in negotiations, perception of behavior strategies of partners in interaction, emotions in the negotiation process, perception of a communicative situation (characteristics), perception of oneself in the process of negotiations, the perception of a negotiating partner, the perception of the effectiveness of negotiations. The study showed that successful intercultural business communication requires a combination of professional and culturally oriented approaches. Attention to cultural features and specifics and consideration of their influence on communication contributes to more effective interaction. However, difficulties arise due to the indirect style of communication and differences in the manifestation of emotions, which can make negotiations difficult. In addition, situations that are threatening to the negotiator's "face" may have an impact on professional and ethnic/ civil identity. As a result of the study, the features of Russian managers'perception of intercultural business communication with Chinese partners were identified, and recommendations were formulated regarding the preparation of Russian managers for international negotiations.